2014
DOI: 10.1152/japplphysiol.00087.2014
|View full text |Cite
|
Sign up to set email alerts
|

Circulating angiogenic cell population responses to 10 days of reduced physical activity

Abstract: Circulating angiogenic cells (CACs) are a diverse group that have been identified as predictors of cardiovascular health and are inversely proportional to cardiovascular disease (CVD) outcomes. Inactivity is a growing concern in industrialized nations and is an independent risk factor for CVD. There is limited evidence regarding the impact of reduced physical activity (rPA) on different CAC populations. The purpose of this study was to evaluate the effect of objectively monitored rPA with maintained energy bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…It is currently unknown if short-term exercise training results in positive endothelial and CAC responses. Significant reductions in CAC number have been observed in our lab with just 10 days of exercise cessation in older athletes (Witkowski et al 2010) and significant reductions in colony-forming unit (CFU) CAC number and intracellular NO have been observed within the same timeframe in younger adults (Guhanarayan et al 2014). We hypothesized that 10 days of endurance exercise training would improve flow-mediated dilation (FMD) and increase CAC number and redox balance in CD34+ CACs of older, previously sedentary adults.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…It is currently unknown if short-term exercise training results in positive endothelial and CAC responses. Significant reductions in CAC number have been observed in our lab with just 10 days of exercise cessation in older athletes (Witkowski et al 2010) and significant reductions in colony-forming unit (CFU) CAC number and intracellular NO have been observed within the same timeframe in younger adults (Guhanarayan et al 2014). We hypothesized that 10 days of endurance exercise training would improve flow-mediated dilation (FMD) and increase CAC number and redox balance in CD34+ CACs of older, previously sedentary adults.…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, Guhanarayan et al (2014) found that 10 days of reduced physical activity is sufficient to decrease CFU number and CFU intracellular NO, but this was not evident in the freshly isolated CD34+ CACs. This suggests that there is a cell-type specific response and that some CACs could adapt or respond more quickly to changes in their intracellular environment.…”
Section: Discussionmentioning
confidence: 92%
“…Likewise, aerobic exercise training also improves the number of resting circulating EPCs in healthy subjects and patients with cardiovascular disease 1 , 8 . Further, reductions in physical activity reduce the number of select angiogenic cell populations 12 , demonstrating that characteristics of physical activity are important for the liberation of these cells into circulation.…”
Section: Introductionmentioning
confidence: 99%
“…43 In younger active men, 10 days of reduced physical activity resulted in diminished CAC colony-forming capacity and CAC NOi. 90 Overall, these studies demonstrate flexibility of CACs, along with increased quantity with repeated bouts of activity in both healthy and diseased populations and reversal with detraining.…”
Section: Effect Of Exercise Training On Epcsmentioning
confidence: 75%